Atkinson-Stiglitz and Ramsey Reconciled: Pareto Efficient Taxation and Pricing under a Break-Even Constraint - Helmuth Cremer; Firouz Gahvari (Center for Economic Studies and ifo Institute (CESifo), 2013)
The Ramsey tax problem examines the design of linear commodity taxes to collect a given tax revenue. This approach has been seriously challenged by Atkinson and Stiglitz (1976) who show that (under some conditions) an optimal income tax makes commodity taxes redundant. In the meantime, the Ramsey setting has had a second life as model of regulatory pricing. Boiteux (1956) studies linear pricing of a regulated multi-product monopoly that has to cover some fixed cost through markups on the different products (equivalent to taxes). While the scope of regulation has declined, Ramsey-Boiteux pricing continues to play an important role. This paper examines if the optimal tax and regulatory pricing approaches to Ramsey pricing can be reconciled. We incorporate the two objectives of revenue raising for financing the government's expenditures and a regulated firm's fixed cost into a single framework. The first major lesson is that the existence of a break-even constraint not only requires taxation of goods produced by the regulated firm, but also the taxation of other goods. Next, we consider the cases of independent Hicksian and Marshallian demand curves. In both the Ramsey solution imply so-called inverse elasticity rules. In the separable Hicksian demand case, the private goods (not included in the break-even constraint) continue to go untaxed as in the Atkinson and Stiglitz setting. In the case where Marshallian demands are independent, the effect of the break-even constraint spills over to the other goods which no longer go untaxed. We continue to get inverse elasticity rules; however, there is no covariance (or similar) term that captures redistributive considerations. Finally, we study the most celebrated general result obtained in the Ramsey model; namely, the (un)equal proportional reduction in compensated demands property. We find that the redistributive considerations are once again replaced by tax revenue terms.
Keywords: H21; 330; Atkinson-Stiglitz theorem; Ramsey; Pareto efficient taxation; break-even constraint